Metabolic, fibrotic and splicing pathways are all altered in Emery-Dreifuss muscular dystrophy spectrum patients to differing degrees. Issue 6 (25th October 2022) - de las Heras, Jose I; Todorow, Vanessa; Krečinić-Balić, Lejla; Hintze, Stefan; Czapiewski, Rafal; Webb, Shaun; Schoser, Benedikt; Meinke, Peter; Schirmer, Eric C
Abstract: Emery-Dreifuss muscular dystrophy (EDMD) is a genetically and clinically variable disorder. Previous attempts to use gene expression changes to find its pathomechanism were unavailing, so we engaged a functional pathway analysis. RNA-Seq was performed on cells from 10 patients diagnosed with an EDMD spectrum disease with different mutations in seven genes. Upon comparing to controls, the pathway analysis revealed that multiple genes involved in fibrosis, metabolism, myogenic signaling and splicing were affected in all patients. Splice variant analysis revealed alterations of muscle-specific variants for several important muscle genes. Deeper analysis of metabolic pathways revealed a reduction in glycolytic and oxidative metabolism and reduced numbers of mitochondria across a larger set of 14 EDMD spectrum patients and 7 controls. Intriguingly, the gene expression signatures segregated the patients into three subgroups whose distinctions could potentially relate to differences in clinical presentation. Finally, differential expression analysis of miRNAs changing in the patients similarly highlighted fibrosis, metabolism and myogenic signaling pathways. This pathway approach revealed a transcriptome profile that can both be used as a template for establishing a biomarker panel for EDMD and direct further investigation into its pathomechanism. Furthermore, the segregation of specific gene changes into distinct groups that appear to correlate with clinical presentation may template development of prognostic biomarkers, though this will first require their testing in a wider set of patients with more clinical information.